The Direction of Violence Against Women Research and Evaluation - Kaukinen, Catherine E. (Women & criminal justice, 2018)
Although researchers have made numerous advances in the understanding of the nature, extent, and dynamics of violence against women (VAW), there is an ever-increasing need for data used in academic research and within policy decision-making to be collected via rigorous methodological designs to accurately measure the incidence and impact of VAW. What is now needed are research collaborations within an interdisciplinary research cluster that will expand understanding of the complex nature of VAW. The current article details an agenda or “call to action” to address deficiencies and advance VAW research, in addition to informing VAW intervention and prevention efforts.